Synthesis of Mono‐fluoroallenes through Copper‐Catalyzed Defluorinative Silylation of α, α‐Difluoroalkylalkynes. Issue 17 (20th June 2022) - Tang, Luning; Pei, Bing‐Bing; Song, Yang; Xue, Fei; Yue, Yanni; Feng, Chao
Comprehensive Summary: A straightforward protocol for the synthesis of mono‐fluorinated allenes via catalytic defluorinative silylation of the readily available α, α‐difluoroalkylalkynes with commercially available copper catalyst and phosphine ligand is described. A broad scope of α, α‐difluoroalkylalkynes were well accommodated and a gram‐scale synthesis demonstrated the synthetic utility of this methodoglogy. Abstract : A Cu‐catalyzed defluorinative silylation of readily available α, α‐difluoroalkylalkynes to access valuable mono‐fluoroallenes under mild conditions was developed.